"It's Like 1998 Again": Why Parents Still Refuse and Delay Vaccines. (August 2021) - Ugale, Jiana L.; Spielvogle, Heather; Spina, Christine; Perreira, Cathryn; Katz, Ben; Pahud, Barbara; Dempsey, Amanda F.; Robinson, Jeffrey D.; Garrett, Kathleen; O'Leary, Sean T.; Opel, Douglas J.
We conducted a qualitative study from 2018 to 2019 to update the reasons why US parents' refuse or delay vaccines. Four focus groups and 4 semi-structured interviews involving 33 primary care pediatric providers were conducted in Washington and Colorado. A thematic analysis was conducted to identify themes related to reasons for parental refusal or delay. Five predominant themes were identified: (1) vaccine safety, (2) relative influence of information sources, decision-makers, and timing, (3) low perceived risk of contracting vaccine-preventable disease, (4) lack of trust, and (5) religious objection. Vaccine safety was the theme mentioned most frequently by providers (N = 45 times by 26 providers) and religious objection to vaccination was referred to the least (N = 6 times by 6 providers). Provider-reported reasons for parental refusal or delay of childhood vaccines in 2018 to 2019 remain similar to those reported in previous studies.